E-052 Institutional experience with the LVIS JR stent for treatment of intracranial aneurysms. (22nd July 2018) - Almandoz, J Delgado; Kayan, Y; Wallace, A; Scholz, J; Milner, A; Fease, J; Mulder, M
Abstract : Purpose: To evaluate the safety and efficacy of the Low-profile Visualized Intraluminal Support (LVIS) Jr stent for treatment of intracranial aneurysms. Methods: We conducted a retrospective review of all consecutive patients with intracranial aneurysms treated with the LVIS Jr stent between June 4th, 2014 and March 31 st, 2018 at our institution. Baseline patient and aneurysm characteristics, procedural variables, complications and aneurysm occlusion at follow-up were recorded. Results: 81 patients underwent 91 procedures to treat 95 intracranial aneurysms using the LVIS Jr stent, 59 women (73%), mean age 59.1 years (median 60 years, 32–83 years). 42 aneurysms were incidental (44%), 41 recurrent (43%), 9 ruptured (10%), and 3 symptomatic (3%). Mean aneurysm size was 6.3 mm (median 5.2 mm, 1.5–31.3 mm), mean neck 3.8 mm (median 2.9 mm, 0.9–13.7 mm), mean dome-to-neck ratio 1.4 (median 1.3, 0.6–2.7). Aneurysm locations were: 36 anterior communicating artery, 26 middle cerebral artery (MCA), 12 basilar tip, 10 anterior cerebral artery, 4 internal carotid artery, 2 posterior communicating artery, 2 vertebral artery and 1 each posterior inferior cerebellar, superior cerebellar and posterior cerebral arteries. Aneurysm embolization techniques were: 91 stent-assisted coiling (96%) and 4 flow diversion (4%). Y-stenting was used for 13 aneurysms (14%), T-stenting for 2 aneurysms (2%) and X-stenting for 1 aneurysm (1%). The LVIS Jr was deployed via a Scepter XC balloon in 49 procedures (54%). Mean packing density was 40% (median 38.5%, 8.8%–90.9%), mean procedure time was 83 min (median 74 min, 35–201 min). The table summarizes treatment-related complications in our cohort. There were no intra-procedural aneurysm/vessel perforations. There were 4 treatment-related complications resulting in a disabling neurological deficit or death (modified Rankin Scale>2, 4.4%). These were 1 MCA perforator infarction on post-operative day (POD) 0; 1 subacute T-stent thrombosis on POD 4; 1 rectus sheath hematoma after percutaneous feeding tube placement leading to severe anemia, hypotension and left MCA territorial infarction on POD 21 in a patient with a ruptured aneurysm; and 1 delayed basilar artery perforator infarction 7 months after Y-stenting of a recurrent giant basilar tip aneurysm. Treatment-related mortality was 2.5%, overall neurological mortality 6.2%. Angiographic follow-up was performed in 58 aneurysms (66%, 30 aneurysms pending follow-up). Follow-up was completed with MR angiography in 54 aneurysms (93%) and catheter angiography in 4 aneurysms (7%). Mean time to last follow-up was 14.1 months (median 6.5 months, 2.9–38.4 months). At last follow-up, 41 aneurysms were completely occluded (70.7%, Raymond 1), 12 had residual neck (20.7%, Raymond 2) and 5 had residual aneurysm (8.6%, Raymond 3). 5 aneurysms were retreated (8.6%). Conclusion: The LVIS Jr stent is a safe and effective tool for the treatment of intracranial aneurysms, achieving high medium-term complete/near complete aneurysm occlusion rates with low treatment-related morbidity and mortality and low re-treatment rates. Disclosures: J. Delgado Almandoz: 2; C; Microvention/Terumo. Y. Kayan: None. A. Wallace: None. J. Scholz: None. A. Milner: None. J. Fease: None. M. Mulder: None.